Citizen's charter driven service area improvement - Fortuito, A.; Bhuiyan, M.; Haque, F.; Shabnam, L.; Krishna, Aneesh; Withana, C. (2016)
A government organisation's capability is reliant on its public service offerings in parallel with acceptable satisfaction level of its service recipients. Government organisations utilise a Citizen's Charter in order to furnish the public with comprehensive details of their service offerings that defines how their overall organisational goals are achieved. Studies on the implementation of Citizen's Charter in developing countries indicated that important social factors were not considered. Social factors can accelerate service delivery with the use of i* in goal-oriented modelling as it represent conditions expected from social actors and their social dependencies. By modelling role dependencies among actors carrying out services in a service area and applying vulnerability and criticality metrics, problem service areas were identified using the Citizen's Charter as a source of these methodologies. Improvements in these problem service areas were based on vulnerability and criticality levels of their corresponding actors. Recommendations to address these service areas include monitoring of key performance indicators of actors and task delegation when necessary.